Odpowiedzi

2009-11-13T19:19:30+01:00
X3+5=2x+5*2x-1
x3-4x=5-1-5
-4x3=-1
4x3=1
x=-5
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-11-13T19:25:29+01:00
X²(x+5)=2(x+5)(2x-1)
x³ + 5x² = 2[2x² - x + 10x - 5]
x³ + 5x² = 4x² - 2x + 20x - 10
x³ + 5x² - 4x² + 2x -20x + 10 = 0
x³ + x² - 18x + 10 = 0
Po podzieleniu z tw.Bezoulta mamy że
x³ + x² - 18x + 10 = (x+5)(x²-4x+2)
Człon x²-4x+2 rozkładamy z delty
delta = (-4)² - 4 * 1*2 = 16 - 8 = 8
pierwiastek z delty = √8 = 2√2
x₁=[-(-4)-2√2]:2 = [4-2√2]:2=2-√2
x₂=[-(-4)+2√2]:2 = [4+2√2]:2=2+√2
Zatem mamy, że
(x+5)(x -[2-√2])(x -[2+√2]) = 0
x+5 = 0 , x = -5
x - 2-√2 = 0, x = 2-√2
x - 2+√2 = 0, x = 2+√2
Rozwiązaniami są -5, 2-√2, 2+√2
2009-11-13T19:30:38+01:00
(x²-4x+2)(x+5)=0
x=-5 ∨ Δ=16-8=8
√Δ=2√2

x1=4-2√2/2=2-2√2 ∨ x2=4+2√2/2=2+2√2 ∨ x=-5